An Empirical Assessment of Divorce Law in Indonesia - Cammack, Mark; Young, Lawrence A.; Heaton, Tim B. (Studia Islamika, 1997)
A discussion of the effect of the marriage Act 1974 against divorce behavior Muslim community in Indonesia can be said to be rare. Various writings that discuss the application of these laws focus more on aspects of institutional, legal and political.DOI:Â 10.15408/sdi.v4i4.766